Role of civil society and press development during Khatami’s presidency in Iran - Zoeram, Vahid Amani (2014)
The aim of this thesis is first, to investigate the evolution of the press as a component of civil society during the Khatami presidency, and second, to examine the role of the political system in these evolutions. The research uses Force Field Theory to analyze the relationships between advocate and opponent forces of civil society in Iran‘s political system during the Khatami presidency. The press, as a predominant component of civil society is a selected case in the thesis. The thesis examines the role of the Executive, the Legislature, and the Judiciary in Iran‘s political system in the changes of the press separately. The research is an explanatory qualitative research. The primary data were collected through semi-structured interviews and secondary data includes international organization's reports and articles in independent journals the time in Iran. The informants are eleven persons who were chosen from three categories of the informants; journalists, experts, and officials. Likewise, the informants were chosen based on purposive sampling method and the study applied qualitative content analysis for analyzing of the data. The outcomes demonstrate how the balance of political forces in the political system had determined the extent of press development in the Khatami era. While reformist forces in certain political institutions had performed as driving forces in the process of press development, conservative forces and some others were the restraining factor. In addition, the results show that Iran's political system has two sources of legitimacy that led to a dichotomy inside the government and this dichotomy caused the formation of two types of elective and appointive institutions within the system. The dichotomy in the political system, on one hand, offered the potential to shape an authoritarian regime that was a barrier to press development. On the other hand, it presented the potential to form a democratic political structure such as during Khatami‘s era that facilitated development of civil society, especially the press.